(untitled) (Research, Society and Development, 2026)
Burns are configured as a serious public health problem, characterized by high morbidity and mortality rates, elevated healthcare costs, and repercussions that go beyond immediate physical damage. In young adults, these injuries acquire particular relevance as they affect individuals in the productive phase of life, resulting in functional limitations, psychological distress, social stigma, and difficulties in returning to work. The objective of this study was to describe the Impacts of burns on young adults, highlighting clinical, psychosocial, and occupational implications. This is a narrative literature review, with a qualitative and exploratory approach, based on publications indexed in the SciELO, LILACS, and BVS databases, covering the period from 2015 to 2023. Of the 350 articles initially identified, 17 met the inclusion criteria and were critically and interpretatively analyzed. The results were organized into five thematic axes: physical impacts; psychosocial and emotional impacts; integral rehabilitation and resilience; the role of nursing in care; and social and occupational reintegration. The literature revealed that burns in young adults lead to a multidimensional process of vulnerability, requiring continuous multiprofessional follow-up and the strategic role of nursing. It is concluded that burns demand interdisciplinary responses, public policies for prevention and inclusion, and the strengthening of care strategies that integrate clinical management, psychosocial support, and occupational reintegration, aiming to ensure quality of life, dignity, and citizenship for survivors.